Maintenance Management Model: an Identification of Key Elements for Value-Based Maintenance Management by Local Authority - Gala Mong, Sylvia; Fikri Mohamed, Sarajul; Mohd. Saidin Misnan, Mohd. (International Journal of Engineering and Technology, 2018)
Maintenance management is a crucial element which governs the economic value of the organization itself. The maintenance management portrays the practice of leading and turning the organization through the deployment and handling of available resources such as financial, human, material, knowledgeable and technology. Consequently, the maintenance management needs to be emphasized by any means of planning, directing, implementing and controlling and several improving methods to achieve economic aspects of the organization. This paper covers part of the study to examine the current practices of the local authorities in Malaysia in maintenance management of public facilities. A systematic literature review has been carried out to identify the existing models and frameworks related to maintenance strategies formulation, selection and its implementation. The literature support for all the key elements needed to achieve value-based maintenance management. Few models of maintenance management were examined to acquire the essential elements before proposing the maintenance management model for local authorities. By analyzing the models, it characterizes the innovations introduced by every author and compares the elements based on maintenance standard requirement for maintenance processes. Also, the discussion is made on the key elements to be included and improved to support organization needs and its application.Â Â